2017
DOI: 10.1002/pola.28614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the structure of titanium–magnesium catalysts on the morphology of polyethylene produced

Abstract: The structure and formation of polyethylene (PE) particles on supported titanium–magnesium catalysts having different structural characteristics (sizes of microcrystallites, mesopores, and subparticles) were studied for the first time. Scanning electron microscopy was used to identify structural elements of the polymer particles formed over such catalysts and to reveal morphological changes in the growing polymer particles when the yield was increased from approximately 0.2 g PE/g catalyst to approximately 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[10] These final fragments are often called primary particles because it is believed that they are the building blocks of the initial catalyst particle. For final polymer particles resulting from ZN catalyst systems supported on magnesium chloride, while primary particles were dispersed in terms of their size, [7,9,12] relatively similar average fragment diameters are reported, namely, 2-5 and 9-13, [13] 2-5, [14] 10-25, [15] and 50 nm. [16] In some studies, radial fragment size gradients were observed [17][18][19] but in majority of researches, fragments were randomly dispersed throughout the whole particle.…”
Section: Doi: 101002/mren202100021mentioning
confidence: 84%
“…[10] These final fragments are often called primary particles because it is believed that they are the building blocks of the initial catalyst particle. For final polymer particles resulting from ZN catalyst systems supported on magnesium chloride, while primary particles were dispersed in terms of their size, [7,9,12] relatively similar average fragment diameters are reported, namely, 2-5 and 9-13, [13] 2-5, [14] 10-25, [15] and 50 nm. [16] In some studies, radial fragment size gradients were observed [17][18][19] but in majority of researches, fragments were randomly dispersed throughout the whole particle.…”
Section: Doi: 101002/mren202100021mentioning
confidence: 84%
“…During polyolefin production, the morphology of the polymer particles strongly affects the equipment operation, and the loss of polymer morphological control may give rise to many industrial operating problems (such as fouling and broadening of the reactor residence-time distribution). It is now widely accepted that the morphology of polymer particles is mainly determined by the morphology of a parent catalyst through the replication phenomenon [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, some problems remain to be solved (e.g., low adduct yield, and complexity of the process). Additionally, in the synthesis of the MgCl 2 support via this method, it is not easy to obtain compact and perfect morphology because it is difficult to control the alcohol content in the MgCl 2alcohol complexes; this affects the porosity and the strength of the catalyst particles and the polymer particle morphology [5,6]. Moreover, the fragmentation of the catalyst particles may result in an undesirable polymer morphology, formation of fines, and reactor fouling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation